The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ajim.23087
|View full text |Cite
|
Sign up to set email alerts
|

Associations of alternative operationalizations of job strain with health and well‐being outcomes in the same multioccupational worker sample

Abstract: ObjectivesThe main goal of this study was to evaluate, in a large, occupationally diverse sample of Colombian workers, the association between alternative methods of operationalizing job strain and various health and well‐being measures using the original Job Content Instrument (Job Content Questionnaire). We examine whether the specific way job strain is operationalized can explains differing variance in the outcomes.MethodsA cross‐sectional survey was conducted using self‐report instruments. A total of 168 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The theoretically broader range of employment options by African Americans in the MIDUS Refresher may have generated the power needed to detect differences. It is also possible that our decision to operationalize job strain in the multiplicative form as opposed to other commonly used strategies 29 may have resulted in the novel association. Pragmatically, the multiplicative form of job strain was selected because we expected and found that elements of the JDC differed by race.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretically broader range of employment options by African Americans in the MIDUS Refresher may have generated the power needed to detect differences. It is also possible that our decision to operationalize job strain in the multiplicative form as opposed to other commonly used strategies 29 may have resulted in the novel association. Pragmatically, the multiplicative form of job strain was selected because we expected and found that elements of the JDC differed by race.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the MIDUS did not use the full battery of items from the Job Content Questionnaire, 29 which can produce meaningful variation in estimates of JDC concepts. 29 Our study focuses on the JDC model; however, we did not include the social support aspect of the model. Therefore, future research may want to include it to further test this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the majority of studies have been done in the healthcare contexts, educational institutions, and manufacturing industries. Only very few of them have examined the constructs of interest and their relationships in more novel occupational contexts, such as the managerial profession (e.g., Pujol-Cols & Lazzaro-Salazar, 2020), or have collected their data in diverse samples of workers with different backgrounds and occupations (e.g., Gómez-Ortiz et al, 2020). We believe that future research should not only involve other regions of Latin America but also include individuals who are expected to be exposed to the highest levels of work-related psychosocial risks, such as police officers, firefighters, social workers, surgeons in ER or trauma units, crisis counselors, hospice caregivers, and emergency dispatchers, among many others.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial risks and health. Overall, research has shown that an increasing exposure to psychosocial risks is associated with a poorer health status (e.g., Gómez-García et al, 2020;Gómez Ortiz et al, 2020). In this regard, previous studies have reported significant correlations between, for instance, high strain (a situation in which the individual faces high job demands and is provided with insufficient job control) or effort-reward imbalance, and common mental disorders (e.g., Araújo et al, 2016;Mattos et al, 2017).…”
Section: Exploration Of the Effects Of Psychosocial Risks On Health And Performancementioning
confidence: 99%